Piper - Clark, Emma Chichester 1955- (Andersen Press, 2005)
This is the story of Piper, a gentle dog, courageous and anxious to please. Unfortunately, a grim man who has no respect for animals buys him, and he won't let Piper have any dinner. So Piper runs away to the big city. There he hurts his leg while trying to save an old lady from being run over. 5 yrs+